The value of motherhood: paid maternity leave discourse in major U.S. media outlets in the years 2014-2018 - Rabenda, Aleksandra (Journal of Education Culture and Society, 2021)
Aim. This article’s goal is to present the discourse concerning paid maternity leaves in the USA in major American media outlets between the years 2014 and 2018. It is an attempt to answer the question whether maternity, caregiving work or family values are contradictory to American work ethic and regulations of the labour market. Methodology. The work is devoted to content analysis of the four most popular American online media, both liberal and conservative. Their content search engines are used to find information and articles on paid maternity leaves and to group them into different categories. Results. Three main categories are distinguished in terms of the content of 302 articles, namely articles with a positive attitude towards paid maternity leaves (248 articles – 82.10%), articles with a negative attitude (20 articles – 6.60%), and neutral articles (34 – 11.30%). In general, Americans see the long-term benefits of paid maternity leaves, but they differ when it comes to the methods of their introduction. Conclusions. There is a conflict between maternity, family values, American work culture, and regulations of the labour market. In American society, individualism, competition, and masculinity of the business culture do not support the values of nurturing and caregiving. Originality. Except for the USA, there is no other country among OECD states which does not provide paid parental leaves for working mothers. Because of the fact that the United States is known to be one of the most developed countries in the world, this information may be considered worth-studying.